2015
DOI: 10.1007/s10291-015-0479-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and evaluation of real-time precipitable water vapor from GLONASS and GPS

Abstract: Abstract:The revitalized Russian GLONASS system provides new potential for real-time retrieval of zenith tropospheric delays (ZTD) and precipitable water vapor (PWV) in order to support time-critical meteorological applications such as nowcasting or severe weather event monitoring. In this study, we develop a method of real-time ZTD/PWV retrieval based on GLONASS and/or GPS observations. The performance of ZTD and PWV derived from GLONASS data using real-time precise point positioning (PPP) technique is carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…The averaged ZTD accuracy was 7.8 mm for GPS-only, 8.1 mm for GLONASS-only, and 7.7 mm for GPS+GLONASS. No obvious biases between GPS-and GLONASSonly PPP-derived ZTD were observed, which were also confirmed by Lu et al (2016) and Dousa and Vaclavovic (2016). Unlike positioning, we found that the ZTD accuracy improved by adding GLONASS observations is not obvious.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The averaged ZTD accuracy was 7.8 mm for GPS-only, 8.1 mm for GLONASS-only, and 7.7 mm for GPS+GLONASS. No obvious biases between GPS-and GLONASSonly PPP-derived ZTD were observed, which were also confirmed by Lu et al (2016) and Dousa and Vaclavovic (2016). Unlike positioning, we found that the ZTD accuracy improved by adding GLONASS observations is not obvious.…”
supporting
confidence: 76%
“…With the model updated (from igs05.atx to igs08.atx), Dousa and Vaclavovic (2016) found that the ZTD biases between GPS and GLONASS did not exist any longer. More recently, Lu et al (2016) analyzed the ZTD derived from GPS-, GLONASS-only, and the combined GPS+GLONASS solutions in a simulated real-time mode and suggested that the ZTD estimates derived from GPS-, GLONASS-only, and the combined GPS+GLONASS solutions agree well with each other.…”
Section: Gps+glonass Ionosphere-free Observation Modelmentioning
confidence: 91%
“…But the radiosonde has been thought to be a useful reference tool for atmospheric sounding [10]. In contrast, the ground-based GNSS technique has several advantages: it has been recognized as an efficient approach to estimate PWV change situations in nearly real time, and it can keep tracking and sensing continuously [11][12][13][14][15][16]. However, GNSS stations, for example, IGS stations, still have low spatial resolution, especially in the ocean area.…”
Section: Introductionmentioning
confidence: 99%
“…Since Bevis et al (1992) [5] first proposed Global Positioning System (GPS) meteorology to remote sensing atmospheric water vapor, GPS meteorology has become an important approach for water vapor detection with high accuracy, all-weather capability, high spatial temporal resolution, and low costs [6][7][8]. With the rapid development of the current global navigation satellite systems (GNSS) constellation, GNSS meteorology has the potential to provide precise PW values with high temporal resolution and is indeed widely used in many meteorological applications, such as numerical weather prediction, water vapor tomography, nowcasting, and severe weather event monitoring [9][10][11][12][13][14][15]. Moreover, water vapor not only contributes significantly to the opacity of the atmosphere in the infrared wavelengths as a greenhouse gas but is also the dominant source of phase fluctuations in radio sciences [16,17].…”
Section: Introductionmentioning
confidence: 99%